Quantitative evaluation of innovation policy based on text analysis - taking Wenzhou as an example - Sheng, Liying; Chen, Gaoxiang; Gao, Yuli; Lin, Qiangqiang; Lin, Xin; Chen, Yaoyao (Asian journal of technology innovation, 2024)
China's high-quality development needs to be driven by innovation. As the birthplace of China's private economy, Wenzhou is an important subject of innovation. The Wenzhou government has put forth many innovation policies, but it is unclear whether the current policies are sensible and the textual contents satisfy the needs of reality. Therefore, this study takes Wenzhou as an example to examine the textual content of innovation policy documents using text analysis method and construct a quantitative framework for innovation policy evaluation. Then we use the PMC-AE index model to evaluate representative policies. The results show that the textual content of the policies is reasonable and in line with the real needs. However, there is still room for improvement, including enriching the nature of the policy, strengthening the combination and application of policy tools, extending the policy's target population and boosting the incentive and guarantee measures of the policy. Both theoretical and practical ramifications emerge from our research. We offer an empirical foundation for the revision, creation, and improvement of the municipal innovation policy on the one hand, while our research also improves the process for assessing policy texts.